Analisa Performa kinerja PLTS Off Grid Yang Dirangkai Seri Paralel untuk Penerangan Ruangan - Erna (Universitas PGRI Palembang, 2023)
Performance analysis of Off Grid PLTS performance which is arranged in parallel series for room lighting. This research begins with the design of PLTS connected in parallel and series-parallel (mixed). This research is divided into two results, namely the preparation of solar panels whose batteries are in full condition and in empty battery condition. This study used 4 solar panels, batteries, Maximum Power Point Tracking (MPPT) and loads in the form of lamps. Data collection was carried out for 8 hours, from 08:00 to 16:00 WIB, measurements were carried out every 30 minutes. In this study the power generated from the parallel arrangement is 32.68 Watt, while in the series-parallel arrangement the value is 33.06 Watt. The ideal combination of solar panel arrangements can be arranged in series-parallel (mixed), a larger voltage in the arrangement of solar panels aims to reduce the voltage drop and power losses, if using a parallel arrangement, you must use a cable with a large size because the parallel arrangement has a value large current, therefore the power distribution is lower, the power is lost along the line.